Fever‐Induced Brugada Syndrome Is More Common Than Previously Suspected: A Cross‐Sectional Study from an Endemic Area. Issue 2 (14th July 2015) - Rattanawong, Pattara; Vutthikraivit, Wasawat; Charoensri, Attawit; Jongraksak, Tanawat; Prombandankul, Awapa; Kanjanahattakij, Napatt; Rungaramsin, Sakda; Wisaratapong, Treechada; Ngarmukos, Tachapong
Abstract : Background: Brugada syndrome (BrS) is defined as presenting of type‐1 Brugada pattern (BrP). BrS can also be induced by fever. This study demonstrated a highest prevalence of fever‐induced BrS ever reported. Method: During May 2014, febrile (oral temperature ≥ 38 °C) and nonfebrile patients underwent standard and high leads (V1 and V2 at 2nd intercostal space) electrocardiogram. Risk factor and cardiac symptoms were recorded. Patients with a persistent of type‐1 BrP after fever had subsided were excluded. The prevalence of BrS, type‐2 BrP and early repolarization pattern (ERP) were demonstrated. Results: A total of 401 patients, 152 febrile, and 249 nonfebrile, were evaluated. BrS was identified in six febrile patients (five males and one female) and two males in nonfebrile patients. The study demonstrated higher prevalence of BrS in febrile group compared to nonfebrile group (4.0% vs 0.8%, respectively, P = 0.037). Among fever‐induced BrS patients, three patients (50.0%) experienced cardiac symptoms before and at the time of presentation and two patients (33.3%) had history of first‐degree relative sudden death. No ventricular arrhythmia was observed. All of type‐1 BrP disappeared after fever had subsided. We found no difference in prevalence of type‐2 BrP in febrile and nonfebrile group (2.0% vs 2.8%, respectively, P > 0.05) as well as ERP (3.3% vs 6.4%, respectively, P > 0.05). Conclusions: Our study showed a highest prevalence of fever induced BrS ever reported. A larger study of prevalence, risk stratification, genetic test and management of fever‐induced BrS should be done, especially in an endemic area.